X-Inactive-Specific Transcript: Review of Its Functions in the Carcinogenesis - Ghafouri-Fard, Soudeh; Dashti, Sepideh; Farsi, Molood; Taheri, Mohammad; Mousavinejad, Seyed Ali (Frontiers in Cell and Developmental Biology, 2021)
X-inactive–specific transcript (XIST) is one of the firstly discovered long non-coding RNAs with prominent roles in the process of X inactivation. Moreover, this transcript contributes in the carcinogenic process in different tissues. In addition to interacting with chromatin modifying molecules, XIST can be served as a molecular sponge for miRNAs to modulate expression of miRNA targets. Most of the studies have indicated an oncogenic role for XIST. However, in prostate cancer, a single study has indicated a tumor suppressor role for this lncRNA. Similar result has been reported for XIST in oral squamous cell carcinoma. In hepatocellular carcinoma, breast cancer, ovarian cancer, osteosarcoma and renal cell carcinoma, different studies have reported inconsistent results. In the present manuscript, we review function of XIST in the carcinogenesis.